Implementasi Web Scraping untuk Pengumpulan Informasi Promo Makanan Menggunakan Klasifikasi Naïve Bayes - Dave Julianno Tandra; Agustinus Noertjahyana; Anita Nathania Purbowo (Jurnal Infra, 2020)
In this day, the delivery of promo information to people can be done easily. Lots of sites that provide information about food promos. Of course the site can help people find the most profitable promos. However, some sites still do not provide complete search features. In addition, there may be promos on the same food supply business, but with a different prices. Of course people will try to find food promos at the best prices. This takes a lot of time, and also less efficient to do. The Naïve Bayes process is also used to determine wheter the promo is in the food category or not. The application was made to collect all promo information from promo provider websites. To do this, we need a server that can retrieve promo data on each promo provider site. After the retriaval process, the data processing and classification process is carried out wheter the promo is in the food category or not. Data that has been processed will be displayed on the application. Based on the result of test that been done on program, program managed to collecting, processing, and displaying data about a promo from promo provider websites. The Naïve Bayes classification process successfully applied to differentiate promos according to category, although there were still shortcomings in the classification process.